2009
DOI: 10.1039/b819061e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a 1,4-benzodiazepine containing palladacycle with in vitro anticancer and cathepsin B activity

Abstract: The reaction of the five-membered C,N-palladacycle [(L)PdCl](2), where LH = 1-methyl-5-phenyl-1H-1,4-benzodiazepin-2(3H)-one, with 1,2-ethanebis(diphenylphosphine), dppe, leads to the formation of the bridged palladacycle. [Pd(2)L(2)(mu-dppe)Cl(2)] 3, which was characterised in solution by (1)H and (31)P NMR spectroscopy and in the solid state by X-ray crystallography. Complex 3 was tested in vitro against a number of cell lines. For example, it inhibited K562 leukaemia cells with an IC(50) value of 4.3 microM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…The 1 H NMR spectra of complexes with pyridine derivatives (1b, 1c, 1d and 2b, 2c) show the resonances attributed to the H 6 of the C 6 H 4 , shifted strongly to upfield. This is also observed in the other complexes [34,38] according to the anisotropic shielding of this proton due to the vicinity to the cis pyridine ligand in the A type structures (Scheme 2) [40,41].…”
Section: Nmr Spectrasupporting
confidence: 61%
“…The 1 H NMR spectra of complexes with pyridine derivatives (1b, 1c, 1d and 2b, 2c) show the resonances attributed to the H 6 of the C 6 H 4 , shifted strongly to upfield. This is also observed in the other complexes [34,38] according to the anisotropic shielding of this proton due to the vicinity to the cis pyridine ligand in the A type structures (Scheme 2) [40,41].…”
Section: Nmr Spectrasupporting
confidence: 61%
“…In this context, several research groups have explored the potential therapeutic applications of cyclopalladated complexes (34, 4146). Regarding kinetoplastid diseases, it has been shown that cyclopalladated complexes were efficacious in reducing the parasite load in an in vivo leishmanial cutaneous model (18) and exhibited trypanocidal potential for Chagas disease treatment (17).…”
Section: Discussionmentioning
confidence: 99%
“…For related structures, see: Zia-ul-Haq et al (2007); Boudina et al (2007); Doubia et al (2007); Sanudo et al (2009); Spencer et al (2009); Swamy et al (2008). For the psychotropic properties of aptazapine [systematic name: 2-methyl-1,3,4,14b-tetrahydro-2H,10H-pyrazino[1,2-a]pyrrolo[2,1-c][1,4]benzodiazepine] and bretazenil [systematic name: t-butyl-8-bromo-11,12,13,13a-tetrahydro-9-oxo-9H-imidazo(1,5-a)pyrrolo(2,1c)(1,4)benzodiazepine-1-carboxylate], see: Silvestri et al (1994); Landquist (1984); Insuasty et al (2008); Bennamane et al (2008); Schutz (1982).…”
Section: Related Literaturementioning
confidence: 99%